Structurally ordered high‐entropy intermetallic nanoparticles with enhanced C–C bond cleavage for ethanol oxidation. Issue 1 (25th May 2022) - Wang, Dongdong; Chen, Zhiwen; Wu, Yujie; Huang, Yu‐Cheng; Tao, Li; Chen, Jun; Dong, Chung‐Li; Singh, Chandra Veer; Wang, Shuangyin
Abstract: Efficient ethanol oxidation reaction (EOR) is challenging due to the multiple reaction steps required to accomplish full oxidation to CO2 in fuel cells. High‐entropy materials with the adjustable composition and unique chemical structure provide a large configurational space for designing high‐performance electrocatalysts. Herein, a new class of structurally ordered PtRhFeNiCu high‐entropy intermetallics (HEIs) is developed as electrocatalyst, which exhibits excellent electrocatalytic activity and CO tolerance for EOR compared to high‐entropy alloys (HEAs) comprising of same elements. When the HEIs are used as anode catalysts to be assembled into a high‐temperature polybenzimidazole‐based direct ethanol fuel cell, the HEIs achieve a high power density of 47.50 mW/cm 2, which is 2.97 times of Pt/C (16.0 mW/cm 2 ). Online gas chromatography measurements show that the developed HEIs have a stronger C–C bond‐breaking ability than corresponding HEAs and Pt/C catalysts, which is further verified by density functional theory (DFT) calculations. Moreover, DFT results indicate that HEIs possess higher stability and electrochemical activity for EOR than HEAs. These results demonstrate that the HEIs could provide a new platform to develop high‐performance electrocatalysts for broader applications. Abstract : A new class of structurally ordered PtRhFeNiCu high‐entropy intermetallics (HEIs) is developed as electrocatalysts for the ethanol oxidation reaction. The assembled high‐temperature polybenzimidazole‐based direct ethanol fuel cell with the HEIs as anode provided a high peak power density of 47.50 mW/cm 2 . These results demonstrate that the HEIs could provide a new platform to develop high‐performance electrocatalysts for broader applications.